2014
DOI: 10.2106/jbjs.n.00541
|View full text |Cite
|
Sign up to set email alerts
|

Survivorship of Hip and Knee Implants in Pediatric and Young Adult Populations

Abstract: Compared with older adults, pediatric patients and young adults undergoing THA and TKA have very different diagnoses, including a high prevalence of tumor. Although the reported rate of revision surgery is currently similar to that for older patients, the number of reported procedures and the follow-up period remain limited. It is important for registries to continue to collect and analyze data relevant to this cohort and to coordinate these activities in order to better understand the safety and effectiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 33 publications
(11 reference statements)
4
49
0
2
Order By: Relevance
“…This finding is comparable with the reports on contemporary cementless THA in adolescents and young adults, which have shown stable implant fixation of femoral stems and acetabular components at intermediate follow-up. 15 , 19 , 21 - 23 …”
Section: Discussionmentioning
confidence: 99%
“…This finding is comparable with the reports on contemporary cementless THA in adolescents and young adults, which have shown stable implant fixation of femoral stems and acetabular components at intermediate follow-up. 15 , 19 , 21 - 23 …”
Section: Discussionmentioning
confidence: 99%
“…I n a study of 1536 children and young adults thirty years of age or younger who were operated on in Australia between 1999 and 2012, we found that patients who underwent hip and knee replacement had very different diagnoses compared with adults, including a high prevalence of tumor (http://dx.doi.org/ 10.2106/JBJS.N.00541) 22 . The revision surgery rate was similar for this population compared with that of older patients.…”
Section: Other Icor Studies Of Devices and Outcomesmentioning
confidence: 99%
“…A review of the Australian registry reported a cumulative revision rate of 4.5% in 297 primary THAs performed in patients 20 years and younger. 3 However, the most common bearing utilized was ceramic-on-ceramic (40%), followed by metal-on-HXLPE (22%), and ceramic-on-HXLPE (8%). One study reported 96% survivorship at an average follow-up of 52 months in patients younger than 20 years with ceramic-onceramic THA, with one revision for acetabular loosening.…”
Section: Discussionmentioning
confidence: 99%